The Diversity and Abundance of Sea Cucumbers in the Batam Waters, Riau Islands - Ismarti Ismarti; Fitrah Amelia; Nurhaty Purnama Sari; Yarsi Efendi; Dian Prasasti; Muslih Anwar (Buletin Oseanografi Marina, 2026)
The exploitation of sea cucumbers in Indonesia has reportedly increased by 66% in the last two decades. This figure is considered the upper limit for sustainable exploitation. The waters of Batam, Riau Islands, are known as one of sea cucumber producers. However, no current status report exists on Batam Island's diversity and abundance of sea cucumbers.  This study aimed to determine the diversity of species and the abundance of sea cucumbers found in Abang, Ngenang, Temoyong Island, and Riau Island. Sampling was carried out quantitatively by applying the quadratic transect method at the three locations. About three transect lines were placed at each station, drawn perpendicular from the coastline towards the sea with a length of 50 m. The distance between each transect line was 50 m, and a 5x5 m plot was placed on each. The results showed that there were six types of sea cucumbers, namely Stichopus nactivagus, Stichopus hermanni, Stichopus monotuberculatus, Holothuria scabra, Holothuria impatiens, and Holothuria leucospila. The species diversity in three locations ranged from 0.214 to 0.314. The abundance of species on Abang, Ngenang, and Temoyong Islands was in the range of 0.073 to 0.1 individual/m2, respectively. The low diversity and abundance indicate high environmental pressure on Batam, Riau Islands sea cucumber populations.